Effects of conformational change and segmental aggregation on photoemission of illuminophores in conjugated polymer MEH-PPV: Blue shift versus red shift - Rakchart Traiphol (2018)
In this contribution, we report experimental results to demonstrate the effects of chain collapse and segmental aggregation of conjugated polymer, poly[2-methoxy, 5-(2′-ethylhexyloxy)-1,4-phenylenevinylene](MEH-PPV), on its photophysics. We have found that the photoemission spectrum of isolated chains in toluene constitutes of high- and low-energy peaks at ∼385 nm and ∼558 nm. This is attributed to simultaneous emissions of short and long illuminophores within the same conjugated chain. When the system is perturbed by addition of a poor solvent, the chains minimize polymer-solvent interactions by undergoing segmental aggregation and/or chain collapse causing drastic change of the optical properties. We demonstrate that the aggregation is responsible for red-shift peaks in absorption and emission spectra detected at ∼550 nm and ∼580 nm, respectively. The chain collapse, on the other hand, causes a blue shift of the spectra. Furthermore, the measurements of emission spectra by using excitation wavelength of 350 nm detect novel high-energy peaks with λmaxat ∼414 nm. The results obtained from temperature-dependent experiments suggest that the detection of high-energy peaks arises from the collapse of individual chains. © 2008 Elsevier B.V. All rights reserved.